Biomechanical Comparison of Inflatable Penile Implants: A Cadaveric Pilot Study. Issue 7 (1st July 2018) - Wallen, Jared J.; Barrera, Enrique V.; Ge, Liehui; Pastuszak, Alexander W.; Carrion, Rafael E.; Perito, Paul E.; Hakky, Tariq S.
Abstract: Background: Throughout the last decade there has been a growing interest in the biomechanical differences between inflatable penile prostheses (IPPs) and their significance with regard to the patient experience. Aim: To present our findings assessing the biomechanical properties of IPPs with and without rear tip extenders (RTEs). Methods: This is a biomechanical study of the 3 most commonly used IPPs (AMS CX, AMS LGX, and Coloplast Titan) as assessed by column compression, modified cantilever deflection, and 3-point bending methods. The IPPs were surgically placed into 3 fresh cadavers via an infrapubic technique by a single large-volume implanter. A biomechanical evaluation of the properties of each IPP inside the fibroelastic tunica albuginea was assessed in blinded testing, and analyses were based on industry standard methods for assessment. Outcomes: Maximum axial load; kink formation; horizontal stiffness; and resistance to 3-point flexure testing were measured. Results: At maximum inflation, all 3 implants had similar performance. Differences appear to be most affected by fill pressures. In fact, only the AMS LGX at less than maximum inflation (LTMI) was unable to consistently withstand the roughly 0.9 kg (2 lbs) of pressure for column load testing mimicking vaginal intromission. The Coloplast Titan showed slightly better rigidity than the AMS LGX and CX devices in horizontal load testing, and, with 3-point flexure testing, the CX showed the best rigidity in the shortest phallus (A). Overall, the Titan showed slightly better rigidity in the longest phallus (C) and the phallus with mild Peyronie's disease (B). Clinical Translations: Penile implants with circumferential expansion had higher rigidity on biomechanical testing and should be considered in a patient's decision during selection of a penile implant. Strengths and Limitations: Strengths include blinding of the biomechanical testing and analyses, surgical procedures performed by a highly experienced surgeon, and that this is the "closest to" in vivo evaluation (inside the tunica albuginea) of penile implant function and properties to date. Weaknesses are that this study was performed in cadavers and not in live patients. It also has a small sample size, including the use of only 3 cadavers, and there was no correlation of performance to patient satisfaction. Conclusion: The results of this study support the conclusion that all devices are capable of functionally restoring erectile capacity. However, we observed that, in general, the 2 circumferentially expanding penile prosthesis showed greater resistance in biomechanical testing when compared with longitudinal and circumferential expanding devices. This should be considered as a guide during device selection for a patient undergoing penile prosthesis.